Application of the used railway brake blocks in production of high-duty cast iron - D. A. Khudokormov; V. A. Alkhimenok; A. T. Skoptsov; V. A. Kishkevich (Литьë и металлургия)
Тhe problem refining of the used brake blocks of passenger cars is examined. There is shown possibility of production of high-test cast iron with a nodular graphite using charging materials with a high content of detrimental impurities. The influence of the melting conditions, modification of melt and chilling of casts on the structure and characteristics of the produced cast iron is studied.